PENGARUH NET PROFIT MARGIN, ARUS KAS OPERASI DAN REPUTASI AUDITOR TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR PERIODE 2014-2017 - Stefanie Stefanie; Loh Wenny Setiawati (Magister Akuntansi, Universitas Atma Jaya Makassar, 2019)
Investments are made by investors to get a return. Return is a profit of an investment. Stock Return has a significant effect in determining the value of company’s stock. Investors will be interested to invest in companies with a high return. This research aimed to analysis the effect of net profit margin, operating cash flow and auditor reputation for the period 2014 – 2016 to stock return for the period 2015 – 2017 on manufacturing companies that listed on Indonesia Stock Exchange. Net profit margin is calculated by using net income after tax divided by total net sales for the period from audited financial statements. This research used secondary data which is from financial reports with purposive sampling. Research sample counted 55 manufacturing companies listed in Indonesia Stock Exchange period 2014 – 2017. The results of this research showed that net profit margin and auditor reputation do not have a significant effect on stock return while operating cash flow has a significant effect on stock return.